Recent advances in contact mechanics : papers collected at the 5th Contact Mechanics International Symposium (CMIS2009), April 28-30, 2009, Chania, Greece - Stavroulakis, Georgios E. (New York : Springer, 2013)
Includes bibliographical references and index